PLL as the Frequency Synthesizer with Continuous Phase Divider - Raičević, A. M.; Popović, B. M. (Elektronika ir Elektrotechnika, 2009)
A PLL frequency synthesizer which (frequency) divider is replaced by a sinusoidal waveform generator has been analyzed. In the generator, n samples of the sinusoidal waveform are generated (created), and (while) the number of discrete points is equal to the dividing module of the divider. By this realization, within every VCO period one sampled value of the sinusoidal function has been generated, it has been sent to the phase detector and together with reference frequency it gives the control voltage. Subsequently, this allows faster reaching of the stable state, which implies high spectral purity of the sinusoidal waveform signal at the synthesizer’s output. This approach keeps all advantages of the PLL synthesizers with look-in tables in terms of stability, and in the same time their architecture is much simpler. Ill. 5, bibl. 5 (in English; summaries in English, Russian and Lithuanian).